Development of Ultrasonic Technique for Detection of Decay in Wooden Cross-Arms - Lai, Sook Kean (2002)
A simple, economic, and accurate nondestructive measurement method has been developed to determine the quality of in-service wooden cross-arms. A wooden cross-arm is part of the pylon normally used to support high-power transmission line. The measurement system uses an ultrasonic pulse, 45kHz, to propagate from transmitter to receiver. The transit time of the pulse is the basic parameter. Investigations show that the transit time is dependent on the distance between two transducers and needs a continuum medium. Other factors such as density, moisture content, fiber direction, continui1y of the medium. and sample thickness also influence the propagation of ultrasound An investigation has been done to find out the optimum condition for detection methods. The optimum condition was determined through various experimental methods such as C-Method, Upper Method, Direct Method, Indirect Method, and Semi-Direct Method.